A multi-approach monitoring of particulate matter, metals and PAHs in an urban street canyon - De Nicola, Flavia; Murena, Fabio; Costagliola, M. Antonietta; Alfani, Anna; Baldantoni, Daniela; Prati, M. Vittoria; Sessa, Ludovica; Spagnuolo, Valeria; Giordano, Simonetta (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2013)
For the first time until now, the results from a prediction model (Atmospheric Dispersion Modelling System (ADMS)-Road) of pollutant dispersion in a street canyon were compared to the results obtained from biomonitors. In particular, the instrumental monitoring of particulate matter (PM10) and the biomonitoring of 14 polycyclic aromatic hydrocarbons (PAHs) and 11 metals by Quercus ilex leaves and Hypnum cupressiforme moss bags, acting as long- and short-term accumulators, respectively, were carried out. For both PAHs and metals, similar bioaccumulation trends were observed, with higher concentrations in biomonitors exposed at the leeward canyon side, affected by primary air vortex. The major pollutant accumulation at the leeward side was also predicted by the ADMS-Road model, on the basis of the prevailing wind direction that determines different exposure of the street canyon sides to pollutants emitted by vehicular traffic. A clear vertical (3, 6 and 9 m) distribution gradient of pollutants was not observed, so that both the model and biomonitoring results suggested that local air turbulences in the street canyon could contribute to uniform pollutant distribution at different heights.
The following values have no corresponding Zotero field: pub-location: TIERGARTENSTRASSE 17, D-69121 HEIDELBERG, GERMANY publisher: SPRINGER HEIDELBERG
Keywords: Holm oak leaves; metals; Moss bags; Naples urban area; PAHs; Pollutant dispersion model

Nutrient dynamics in litter mixtures of four Mediterranean maquis species decomposing in situ - Maisto, Giulia; De Marco, Anna; Meola, Angela; Sessa, Ludovica; Virzo De Santo, Amalia (Soil Biology and Biochemistry, 2011)
In natural conditions, litters shed from different species become mixed with each other, and decompose together. Most studies deal with decomposition of individual species; few studies investigate the inﬂuence of litter mixing on decomposition and nutrient dynamics; the results are contradictory as positive, negative, or no effect, of litter mixing have been observed. In this study we test the hypothesis: i) that litter mixing in the Mediterranean maquis, a nutrient poor, high diversity ecosystem, produces non-additive effects on nutrient dynamics; ii) that the effects vary with the composition in species of the mixture and with the relative amount of the species component the mixture. Two types of 3-species mixtures were set up; one contained three sclerophylls, Phillyrea angustifolia, Pistacia lentiscus and Quercus ilex; the other contained the ﬁrst two species with the mesophyll Cistus. Litterbags, containing monospeciﬁc litters and even and uneven mixtures, were incubated under natural condition in situ; even mixtures had the 3 species in equal proportion, whereas uneven mixtures had one of the species as dominant (50%) and the other two species in equal proportion (25%:25%). Litterbags were retrieved after 92, 188 and 403 days; litters from the mixtures were separately analyzed for mass loss and content of nitrogen (N), potassium (K), sodium (Na), calcium (Ca), magnesium (Mg), manganese (Mn), iron (Fe), copper (Cu), and zinc (Zn). Results indicate that mixing inﬂuences the dynamics of N, Mn, Ca, Mg, Fe, Cu and Zn, but scarcely affects the dynamics of K and Na. The comparison of observed to expected values for changes of nutrients in litterbags indicates the occurrence of non-additive effects of litter mixing on movements of N, Fe, Cu, and Zn to or from the litterbags containing the mixtures. The effects depend on the composition in species of the mixture, whereas the relative amount of the species component the mixture is not relevant.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Interactions among litters; Lignin; litter decomposition; Manganese; Non-additive effects of litter mixing